TEACHING LISTENING BY USING VIDEO MEDIA TO THE EIGHTH GRADE STUDENTS OF SMP N 3 LAHAT - Juliza Fitri, Wanda; Mulyadi; Rosmiyati, Evi (Universitas PGRI Palembang, 2024)
The objective of this study is to find out the effectiveness of teaching listening by using video media to improve students’ listening skills. The writer used pre-experimental design with one group pre-test and post-test design. The data of this study collected by means of written test. The sample of this study is 32 students. The results of this study showed it was effective to teaching listening by using video media. The writer found that the students’ average scores in the pre-test was 59.5 and in the post-test was 76.7. The scores showed that the average scores in the post-test was higher than the students’ average in the pre-test. The writer also found that the result of the matched t-test calculation between the students’ scores in post-test and pre-test was 13.983. The scores were higher than the critical value of the t-table with 5% (0.05) significance level in one-tailed testing 1.695. It means that video media could improve the students’ listening skills.